Facile synthesis of 9H-pyrrolo[1, 2-a]indoles via Brønsted acid catalyzed cascade reactions. Issue 97 (19th November 2019) - Xu, Kunhua; Chen, Wenming; Lin, Jin; Chen, Guifang; Wang, Biao; Tian, Xu
Abstract : A Brønsted acid system promotes the Friedel–Crafts alkenylation/1, 6-addition/condensation cascade reaction of ynones with indoles to access 9 H -pyrrolo[1, 2- a ]indoles. Abstract : An efficient Brønsted acid catalyzed Friedel–Crafts alkenylation/1, 6-addition/condensation cascade reaction has been developed. This protocol enables effective access to various highly functionalized 9 H -pyrrolo[1, 2- a ]indoles in moderate to high yields. Mechanistic studies indicate that the in situ vinylogous reactivity intermediate might be formed in the catalytic system.